Right-wing populism and the criminalization of sea-rescue NGOs: the 'Sea-Watch 3' case in Italy, and Matteo Salvini's communication on Facebook. (April 2021) - Berti, Carlo
The contemporary outbreak of right-wing populism in combination with increasing migratory flows toward Europe raises concerns about the social construction of migrations and migrants and the policy orientations toward them. Research indicated worrying tendencies to perceive migrations negatively and criminalize migrants. However, this paper focuses on a different tactic adopted by a number of populist forces: the criminalization of sea-rescue NGOs. In particular, it presents the case-study of Sea-Watch 3, an NGO sea-rescue vessel which docked in Italy with several migrants on board in June 2019, after a long struggle with Minister of Internal Affairs Matteo Salvini, the leader of the League (a right-wing, anti-migrants populist party). By means of content analysis, the paper discusses Salvini's Facebook communication strategy about the event. The aim of this study is to cast new light on how the criminalization of NGOs can be exploited to reinforce other aspects of right-wing populism, such as anti-elitism, nationalism, exclusionary politics, personalization, and polarization. In this respect, the implications of criminalizing sea-rescue NGOs for policy orientations and policymaking are also highlighted.